Rafael Díaz Ycaza: un Prometeo de las letras - Dávila Vázquez, Jorge (2013)
The article reviews the literary career of one of the greatest Guayaquileño writers of the post Thirty Generation period: Rafael Díaz Ycaza. An extraordinary storyteller, the author begins with a realist debt very close to that of his predecessors but, little by little, he transitions to the poetic and fantastic, never detaching himself from realism, in his penetrating analysis of subjects closely related to his environment: maritime adventure, the confrontation with death, an obsession with suicide –perceptible in some of his best works, including “Rosamel” and “Las equivocaciones” (The mistakes). A poet of remarkable qualities, he is, on more than one occasion, at the same height as his great contemporaries: David Ledesma Vásquez, Ileana Espinel Cedeño and Fernando Cazón Vera, the outstanding names of the poetry of their city (Guayaquil). The subjects are close to those of his fiction, but his song of the city predominates, which occurs in different creative moments.